2021
DOI: 10.1063/5.0029532
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly large remanent polarization of Hf0.5Zr0.5O2 metal–ferroelectric–metal capacitor fabricated without breaking vacuum

Abstract: We introduce an Atomic Layer Deposition (ALD) technique referred to here as Sequential, No-Atmosphere Processing (SNAP) to fabricate ferroelectric Hf0.5Zr0.5O2 capacitors in Metal–Ferroelectric–Metal (MFM) structures. SNAP involves the ALD of each layer sequentially while maintaining the sample under vacuum process conditions without ambient exposure during the entire sequential deposition processes. We first use plasma enhanced ALD to fabricate 002-textured TiN films and study the degree of texture and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Note that the high carbon concentration found by XPS is not only due to the presence of unreacted ligands from ALD metalorganic precursors, but also accounts for adsorbed hydrocarbons from exposure to the atmosphere. The XPS quantification is consistent with our previous depth profiling XPS work, which suggested ∼20 atom % C on the surface of the film, which decreases to <5 atom % when measured via depth profiling XPS within the MFM stack …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Note that the high carbon concentration found by XPS is not only due to the presence of unreacted ligands from ALD metalorganic precursors, but also accounts for adsorbed hydrocarbons from exposure to the atmosphere. The XPS quantification is consistent with our previous depth profiling XPS work, which suggested ∼20 atom % C on the surface of the film, which decreases to <5 atom % when measured via depth profiling XPS within the MFM stack …”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure , HZO-O 2 * possesses a more pronounced TiO x layer than HZO-H 2 O. Given that the bottom TiN used in our MFM capacitors is strongly 001-textured, the inclusion of a TiO x layer may render an “interface-breaking” effect, i.e., a disruption in how the underlying 001-textured TiN may influence the formation of the texture of HZO. The interface-breaking of TiN/HZO in HZO-O 2 * could thus encourage the growth of more energetically favorable HZO {111} planes which have a lower surface energy compared to the {001} planes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the diffraction peak shifted toward higher angles when the doping concentration of La was increased to 11 at%, suggesting the formation of a t ‐phase. [ 17,18 ] Owing to structural expansion, the diffraction peak shifted back to a lower angle when the doping concentration of La was further increased to 17 and 23 at%; this indicates the formation of a cubic phase. [ 16,17 ] Although a detailed analysis is required to accurately determine the crystalline phases, peak shift observations can be used as a reference for crystalline phase estimations.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the ferroelectric behavior arises due to the formation of a noncentrosymmetric orthorhombic Pca 2 1 phase, , where the oxygen ions are able to switch between two stable positions, which correspond to two stable polarization states . The formation of orthorhombic HZO was evidenced by Müller et al It has been found to be favored by the postmetallization anneal, , which induces sufficient strain within HZO to create favorable conditions for the growth of orthorhombic Pca 2 1 with ferroelectric properties. Similar to HfO 2 , the inclusion of dopants with a size larger or smaller than that of Hf and Zr ions, which are responsible for the distortion and internal stress within HZO, can have a beneficial effect on the ferroelectric properties, especially on the endurance .…”
Section: Introductionmentioning
confidence: 99%